2009
DOI: 10.1016/j.cor.2008.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling permutation flowshops with initial availability constraint: Analysis of solutions and constructive heuristics

Abstract: In this paper, we address the problem of scheduling a set of jobs in a flowshop with makespan objective. In contrast to the usual assumption of machine availability presented in most research, we consider that machines may not be available at the beginning of the planning period, due to processing of previously scheduled jobs. We first formulate the problem, analyse the structure of solutions depending on a number of factors (such as machines, jobs, structure of the processing times, availability vectors, etc.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…This is not only motivated by breakdowns or planned maintenance, but also because machines are busy processing already scheduled jobs. However, existing research on this topic is almost inexistent (see Besbes et al, 2010 or Perez-Gonzalez andFraminan, 2009 for initial works on the topic).…”
Section: "New" Types Of Constraintsmentioning
confidence: 99%
“…This is not only motivated by breakdowns or planned maintenance, but also because machines are busy processing already scheduled jobs. However, existing research on this topic is almost inexistent (see Besbes et al, 2010 or Perez-Gonzalez andFraminan, 2009 for initial works on the topic).…”
Section: "New" Types Of Constraintsmentioning
confidence: 99%
“…RS and RT are two strategies which attach new orders to the end of the existing schedule. It has been confirmed that rescheduling the remaining jobs of the old order can provide a higher quality schedule [13,16,24]. However, no reactive methods can provide high-quality solutions with order mixing, therefore missing the opportunity of optimized schedule [25].…”
Section: Related Workmentioning
confidence: 96%
“…However, this assumption can be only applied in real-world problems if it is the first time that jobs are to be scheduled in the shop, or a long period without processing jobs has occurred. Since these assumptions are not common in practice, [30] consider restrictions in the initial availability of the machines for the minimisation of the makespan. Results show how the initial availability assumption make the problem easier (again in the sense of increasing the probability of finding a 'good' solution), specially if structured processing times are considered.…”
Section: Introductionmentioning
confidence: 99%